Ravenne de la Zona dantesca à la Zona del silenzio - Renard, Thomas (Opus Incertum, 2021)
Based on archival material and the available bibliography, this article traces the complex history of the area surrounding the tomb of Dante Alighieri and the Basilica of San Francesco in Ravenna. It focuses on the period running from the commemorations of the sixth centenary of Dante’s birth in 1865 to the inauguration of the Zona del silenzio in 1936. The end of the 19th century was marked by the failure of important monumental projects. The sixth centenary of Dante’s death in 1921 was the first important phase of transformation, seeking to recreate the appearance of a medieval past. Subsequently, during the Fascist period, several projects, notably those by Giulio Ulisse Arata and Gustavo Giovannoni, attempted to extend the intervention to the urban scale, which, through aborted projects and partial realisations, led to the creation of the Zona del Silenzio. Through the interplay of local and national actors and the key role of Corrado Ricci, the article analyses the difficulties of developing an area that symbolically embodies Italy’s tribute to the national poet.